Observation of the decay B0s → K0pp̄ and measurement of the B0(s) → K0pp̄ branching fractions - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Journal of high energy physics, 2025)
A study of the charmless baryonic decays $$ B_{(s)}^0→ K^0p\overline{p} $$is presented, where $$ B_{(s)}^0 $$denotes either a B0 or a $$ B_s^0 $$meson. The analysis is based on proton-proton collision data collected by the LHCb experiment at centre-of-mass energies of 7, 8, and 13 TeV, corresponding to an integrated luminosity of 9 fb−1. The decay $$ B_s^0→ K^0p\overline{p} $$is observed for the first time, with a measured branching fraction of (9.14 ± 1.69 ± 0.90 ± 0.33 ± 0.20) × 10−7 and a significance of 5.6σ. The uncertainties respectively account for statistical and systematic contributions, the precision of the branching fraction of the normalisation channel B0 → K0π+π− and the fragmentation fraction ratio fs/fd. The branching fraction determined for $$ B^0→ K^0p\overline{p} $$is (2.82 ± 0.08 ± 0.12 ± 0.10) × 10−6, which is the most precise measurement to date.
Im Text ist "0" jeweils hochgestellt, "s" und (s") tiefgestellt
The LHCb collaboration: R. Aaij, A. S. W. Abdelmotteleb, C. Abellan Beteta, F. Abudinén, T. Ackernley, A. A. Adefisoye, B. Adeva, M. Adinolfi, P. Adlarson, C. Agapopoulou, C. A. Aidala, Z. Ajaltouni, S. Akar, K. Akiba, P. Albicocco, J. Albrecht, F. Alessio, Z. Aliouche, P. Alvarez Cartelle, R. Amalric, S. Amato, J. L. Amey, Y. Amhis, L. An, L. Anderlini, M. Andersson, A. Andreianov, P. Andreola, M. Andreotti, D. Andreou, A. Anelli, D. Ao, F. Archilli, M. Argenton, S. Arguedas Cuendis, A. Artamonov, M. Artuso, E. Aslanides, R. Ataíde Da Silva, M. Atzeni, B. Audurier, D. Bacher, I. Bachiller Perea, S. Bachmann, M. Bachmayer, J. J. Back, P. Baladron Rodriguez, V. Balagura, A. Balboni, W. Baldini, L. Balzani, H. Bao, J. Baptista de Souza Leite, C. Barbero Pretel, M. Barbetti, I. R. Barbosa, R. J. Barlow, M. Barnyakov, S. Barsuk, W. Barter, J. Bartz, S. Bashir, B. Batsukh, P. B. Battista, A. Bay, A. Beck, M. Becker, F. Bedeschi, I. B. Bediaga, N. A. Behling, S. Belin, K. Belous, I. Belov, I. Belyaev, G. Benane, G. Bencivenni, E. Ben-Haim, A. Berezhnoy, R. Bernet, S. Bernet Andres, A. Bertolin, C. Betancourt, F. Betti, J. Bex, Ia. Bezshyiko, O. Bezshyyko, J. Bhom, M. S. Bieker, N. V. Biesuz, P. Billoir, A. Biolchini, M. Birch, F. C. R. Bishop, A. Bitadze, A. Bizzeti, T. Blake, F. Blanc, J. E. Blank, S. Blusk, V. Bocharnikov, J. A. Boelhauve, O. Boente Garcia, T. Boettcher, A. Bohare, A. Boldyrev, C. S. Bolognani, R. Bolzonella, R. B. Bonacci, N. Bondar, A. Bordelius, F. Borgato, S. Borghi, M. Borsato, J. T. Borsuk, E. Bottalico, S. A. Bouchiba, M. Bovill, T. J. V. Bowcock, A. Boyer, C. Bozzi, J. D. Brandenburg, A. Brea Rodriguez, N. Breer, J. Brodzicka, A. Brossa Gonzalo, J. Brown, D. Brundu, E. Buchanan, L. Buonincontri, M. Burgos Marcos, A. T. Burke, C. Burr, J. S. Butter, J. Buytaert, W. Byczynski, S. Cadeddu, H. Cai, A. Caillet, R. Calabrese, S. Calderon Ramirez, L. Calefice, S. Cali, M. Calvi, M. Calvo Gomez, P. Camargo Magalhaes, J. I. Cambon Bouzas, P. Campana, D. H. Campora Perez, A. F. Campoverde Quezada, S. Capelli, L. Capriotti, R. Caravaca-Mora, A. Carbone, L. Carcedo Salgado, R. Cardinale, A. Cardini, P. Carniti, L. Carus, A. Casais Vidal, R. Caspary, G. Casse, M. Cattaneo, G. Cavallero, V. Cavallini, S. Celani, S. Cesare, A. J. Chadwick, I. Chahrour, H. Chang, M. Charles, Ph. Charpentier, E. Chatzianagnostou, M. Chefdeville, C. Chen, S. Chen, Z. Chen, A. Chernov, S. Chernyshenko, X. Chiotopoulos, V. Chobanova, M. Chrzaszcz, A. Chubykin, V. Chulikov, P. Ciambrone, X. Cid Vidal, G. Ciezarek, P. Cifra, P. E. L. Clarke, M. Clemencic, H. V. Cliff, J. Closier, C. Cocha Toapaxi, V. Coco, J. Cogan, E. Cogneras, L. Cojocariu, S. Collaviti, P. Collins, T. Colombo, M. Colonna, A. Comerma-Montells, L. Congedo, A. Contu, N. Cooke, C. Coronel, I. Corredoira, A. Correia, G. Corti, J. Cottee Meldrum, B. Couturier, D. C. Craik, M. Cruz Torres, E. Curras Rivera, R. Currie, C. L. Da Silva, S. Dadabaev, L. Dai, X. Dai, E. Dall’Occo, J. Dalseno, C. D’Ambrosio, J. Daniel, P. d’Argent, G. Darze, A. Davidson, J. E. Davies, O. De Aguiar Francisco, C. De Angelis, F. De Benedetti, J. de Boer, K. De Bruyn, S. De Capua, M. De Cian, U. De Freitas Carneiro Da Graca, E. De Lucia, J. M. De Miranda, L. De Paula, M. De Serio, P. De Simone, F. De Vellis, J. A. de Vries, F. Debernardis, D. Decamp, S. Dekkers, L. Del Buono, B. Delaney, H.-P. Dembinski, J. Deng, V. Denysenko, O. Deschamps, F. Dettori, B. Dey, P. Di Nezza, I. Diachkov, S. Didenko, S. Ding, L. Dittmann, V. Dobishuk, A. D. Docheva, C. Dong, A. M. Donohoe, F. Dordei, A. C. dos Reis, A. D. Dowling, W. Duan, P. Duda, M. W. Dudek, L. Dufour, V. Duk, P. Durante, M. M. Duras, J. M. Durham, O. D. Durmus, A. Dziurda, A. Dzyuba, S. Easo, E. Eckstein, U. Egede, A. Egorychev, V. Egorychev, S. Eisenhardt, E. Ejopu, L. Eklund, M. Elashri, J. Ellbracht, S. Ely, A. Ene, J. Eschle, S. Esen, T. Evans, F. Fabiano, S. Faghih, L. N. Falcao, B. Fang, L. Fantini, M. Faria, K. Farmer, D. Fazzini, L. Felkowski, The LHCb collaboration
Gesehen am 12.02.2026